2011
DOI: 10.1073/pnas.1108460108
|View full text |Cite
|
Sign up to set email alerts
|

Reactibodies generated by kinetic selection couple chemical reactivity with favorable protein dynamics

Abstract: Igs offer a versatile template for combinatorial and rational design approaches to the de novo creation of catalytically active proteins. We have used a covalent capture selection strategy to identify biocatalysts from within a human semisynthetic antibody variable fragment library that uses a nucleophilic mechanism. Specific phosphonylation at a single tyrosine within the variable light-chain framework was confirmed in a recombinant IgG construct. Highresolution crystallographic structures of unmodified and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 40 publications
5
52
0
Order By: Relevance
“…Recently, a unique catalytic antibody A17 named a “reactibody” was prepared by Smirnov et al (11) by employing an innovative idea and technique. It could cleave paraoxon and possesses an unusual deep cavity at the interface of V L and V H .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a unique catalytic antibody A17 named a “reactibody” was prepared by Smirnov et al (11) by employing an innovative idea and technique. It could cleave paraoxon and possesses an unusual deep cavity at the interface of V L and V H .…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances have demonstrated that CYP3A4 cooperativity involves the binding of multiple (at least 2) substrate molecules to the binding pocket and represents a case of true allostery characterized by effector-induced conformational transitions (Davydov and Halpert, 2008). On the basis of the above theory and our results, the differential effects of PXT on the metabolism of MDZ, similar to the effectors of citral, 6-gingerol, and D-limonene (Zhang and Lim, 2008), can be explained by a two-site model (Korzekwa et al, 1998;Domanski et al, 2001) or a multi-site model (Kenworthy et al, 2001;Manoj et al, 2010;Smirnov et al, 2011) of CYP3A4. It can be hypothesized that PXT can bind to one defined site that is also occupied by MDZ in the position required for 4-hydroxylation (or 19-hydroxylation) and that both substrates can displace each other.…”
Section: Discussionmentioning
confidence: 87%
“…The oligonucleotides VH.link (5 -ACT CCC GCC ACC TCC TGA AGA GAC GGT ) and VL.link (5 -GGT GGC GGG AGT GAA ATT GTG CG-3 ) that include overlapping segments were used in order to reduce the original linker [(G 4 S) 3 ] to G 4 S. The conditions for the amplifications, overlapping reaction and cloning into the expression vector pSyn1 were the same as previously described [20].…”
Section: Construction Of Diabody 6009fmentioning
confidence: 99%
“…Antibody engineering technologies have evolved rapidly over the last three decades, and it is now possible to produce a set of different antibody fragments for use in a wide range of applications that avoid the process of immunizing an animal [1][2][3]. Due to their versatility, recombinant antibody fragments have become important tools in research, diagnostics and therapy [4].…”
Section: Introductionmentioning
confidence: 99%